Study of the Form and Meaning of the Nawa Gapura Marga Raja as an Artefact of the Cirebon Cultural Community: Form and Meaning Nawa Gapura Marga Raja - Fadhly . Abdillah; Setiawan Sabana; Imam Santosa (JOMANTARA, 2021)
A work of traditional culture by the geniuses of Cirebon's past, named Nawa Gapura Marga Raja, is one of the historical buildings that are still sacred. There are 9 doors or gates, each of which is gathered in one area of ​​the building. The form and meaning of the number of gates for the author is a very interesting phenomenon to study, its relation to cultural expressions that allow so many symbolic values ​​to be interpreted. This study of form and meaning aims to analyze and gain knowledge related to the form and visual meaning of the gates in this building. To find out the meaning of the physical form of Nawa Gapura Marga Raja, this study uses an art criticism approach from Edmund Burke Feldman with the visual narration method of Gerard Genette. In the process, the research goes through the following stages; literature study, observation, and conducting interviews with related parties. From the results of the analysis, it is understood that the structure of the form and layout of the building is heavily influenced by the spatial concept of primordial culture mixed with a new culture, so that it represents a myth, also has meanings that are closely related to religious teachings, culture and leadership values. Keywords: form, art criticism, visual narrative, meaning, nawa gapura marga raja